Perencanaan Bangunan Pengendali Sedimen Pada Jembatan Kereta Api Kota Madiun - Agastya, Adya; Imron, Nanda Ahda (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2020)
Regarding the construction of a double track railway crossing the city of Madiun, precisely in the Nambangan Lor area, the constructions of a new bridge on the south side of the previous bridge is occured. The condition of the Bengawan river in the rainy season has a large water discharge which causes a large flood. The impact of the flood caused scours of sediment in the river and made it possible to erode the sediment around the bridge abutment. Therefore, to reduce the impact of scour sediment on the abutment, a sediment control building is needed. In order to plan this construction, we need minimum rain cycle data from three rain stations which are needed for hydrological analysis, annual rain plan determination, annual flooding and hydraulics analysis to determine the dimensions of the building. The result of this planning obtained that the flood discharge period of 100-year return is 1557,992127 m3 / sec, the flow velocity is 8.319945 m / sec, the width of the boiler light is 3,362374 m, the depth of the foundation is 2,971201 m, the thickness of the floor is 2,1143 m, and floor length is 16.5657 m.